Dietary polyphenol quercetin targets pancreatic cancer stem cells - Zhou, Wei; Kallifatidis, Georgios; Baumann, Bernd; Rausch, Vanessa; Mattern, Jürgen; Gladkich, Jury; Giese, Nathalia; Moldenhauer, Gerhard; Wirth, Thomas; Büchler, Markus W.; Salnikov, Alexey V.; Herr, Ingrid (International journal of oncology, 2010)
According to the cancer stem cell hypothesis the aggressive growth and early metastasis of pancreatic cancer may arise through dysregulation of self-renewal of stem cells in the tissue. Since recent data suggest targeting of cancer stem cells by some dietary agents we studied the effect of quercetin, a major polyphenol and flavonoid commonly detected in many fruits and vegetables. Using in vitro and in vivo models of pancreatic cancer stem cells we found quercetin-mediated reduction of self-renewal as measured by spheroid and colony formation. Quercetin diminished ALDH1 activity and reverted apoptosis resistance as detected by substrate assays, FACS and Western blot analysis. Importantly, combination of quercetin with sulforaphane, an isothiocyanate enriched in broccoli, had synergistic effects. Although quercetin led to enhanced binding of the survival factor NF-κB, co-incubation with sulforaphane completely eliminated this pro-proliferative feature. Moreover, quercetin prevented expression of proteins involved in the epithelial-mesenchymal transition, which was even stronger in presence of sulforaphane, suggesting the blockade of signaling involved in early metastasis. In vivo, quercetin inhibited growth of cancer stem cell-enriched xenografts associated with reduced proliferation, angiogenesis, cancer stem cell-marker expression and induction of apoptosis. Co-incubation with sulforaphane increased these effects and no pronounced toxicity on normal cells or mice was observed. Our data suggest that food ingredients complement each other in the elimination of cancer stem cell-characteristics. Since carcinogenesis is a complex process, combination of bioactive dietary agents with complementary activities may be most effective.